Robustness analysis in a TODIM-based multicriteria evaluation model of rental properties - Pereira, Javier; Gomes, Luiz Flavio Autran Monteiro; Paredes, Fernando (Technological and Economic Development of Economy, 2014)
A new robustness analysis framework is proposed where robustness of a solution in a decision aiding process is measured as the distance from that solution to an expected outcome, chosen by the decision-aiding analyst. The framework is explained by the application of the TODIM method of multicriteria decision aiding to the problem of predicting rental ranges for properties in a Chilean city. Therefore, the robustness concern concentrates on changes in criteria weights as well as in trade-off rates, as they are defined in the method. Two main contributions are introduced: a local robustness measure, defined in terms of a distance among rankings; and a global robustness measure, as an adaptation of the minimax-regret rule to select a global robust solution, i.e. a ranking produced by TODIM.